Y is for Yam - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Africa is responsible for 96% of the world's production of food yams; producing almost 30 millions tons a year. Most of the remainder is produced in the Caribbean and Pacific. For 150 million people, yam is, together with cassava and potato, a food...